Impact of hypercholesterolemic diet on the Ca-regulating hormones and some minerals in male rats - Al Ameer , Duaa Raad Abd; Albazi , Wefak; muhammed, Hayder Ali (Journal of Kerbala for Agricultural Sciences, 2024)
Abstract Cholesterol is a fatty substance essential for the body. However, excessive amounts can lead to health problems. The study's objective was to investigate the potential effects of a diet high in cholesterol on the hormonal regulation of calcium metabolism and the balance of essential minerals in the body. Twenty male rats aged (1.5-2 ) months were divided as follows, 2 groups : (10) rats were fed a normal diet, and (10) rats were fed a high cholesterol diet(2%) for 8 weeks HCD group. Blood samples were collected after the end of the experiment for physiological and biomarker parameters calculation, as well as lipid profile, minerals, hormones, and antioxidants, after the end of the experiment (8 weeks). The results showed a significant elevation in serum of serum lipid profile (TG, TC, LDL) and decreased (HDL), an elevation in serum of Malondialdehyde and (MDA) and an increase in serum calcium levels. Calcitonin levels, parathyroid hormone, and Vit.D levels showed a significant decrease in serum Glutathione (GSH) levels in the cholesterol group compared to the control group. The study concludes that a hypercholesterolemic diet can lead to Dysregulation of Ca-regulating hormones, Dysregulation of parathyroid hormone (PTH), and Calcitonin, which may disrupt the delicate balance of calcium metabolism in the body. This Dysregulation could result in increased bone resorption, altered calcium absorption and excretion, and imbalances in other minerals involved in bone health and overall physiological processes.